ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN KREDIT SUB SEKTOR PERTANIAN DI BANK NTT CABANG BAJAWA KABUPATEN NGADA - Toda, Anthonius Ardianto Djawa; Tiwu, Maria Indriyani Hewe (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 8 (2024): Vol.13.No.8. AGUSTUS 2024 [545-633], 2024)
This study aims to analyze the factors that influence the rate of return on credit in the agricultural sub-sector in NTT banks and to analyze the rate of return on credit in the agricultural sector. The data method used is qualitative research using data reduction analysis, data presentation, verification and conclusions. The results of the study show that the relationship between business characteristics and the rate of return on micro business credit is influenced by things such as business experience, business turnover and profits. Business experience greatly affects the rate of credit returns. The relationship between Credit Characteristics and Micro Business Credit Repayment Rates can be influenced by the loan amount, repayment period and borrowing experience. The greater the loan amount borrowed by the debtor, the greater the return, because in addition to paying off credit, the debtor also pays interest and installments. The repayment period also affects the rate of return on micro business credit because the longer the credit repayment period means that the monthly installment burden that must be paid is relatively lighter, when compared to a faster repayment period with the same loan amount. Keywords: Credit Return, Micro Business, and Agriculture